FORMULASI PEMBUATAN BIOGREASE DENGAN BASE OIL EPOKSI RBDPO - M Luqmanul Hakim; Erliza Hambali; Dwi Setyaningsih (Department of Agroindustrial Technology, Bogor Agricultural University, 2022)
Biogrease is a semi-solid lubricant produced using vegetable oil. The biogrease consists of base oil andthickening agent. Base oil modification is done to change properties such as viscosity, adhesive properties to iron,etc. which have an impact on tribological properties. One of the modifications made is the epoxidation of the baseoil to increase the viscosity value. Epoxidation of the olein fraction /RBDPO (Refined Bleached Deodorized PalmOlein) was carried out by reacting olein with acetic acid and peroxide acid. This study aimed to find the best timein the synthesis of RBDPO epoxy base oil, to study the effect of variations in % thickener on the characteristics ofbiogrease, and the best characteristics of biogrease produced from RBDPO epoxy base oil. The epoxidation wascarried out with a ratio of RBDPO : acetic acid : peroxide acid of 1: 5: 2 at a temperature of 50°C, with variousexperimental times of 3 hours, 4 hours, and 5 hours. The epoxidation results calculated the oxirane number andiodine number with two replications, then analyzed ANOVA statistics and LSD test. Furthermore, the bestepoxidation results were formulated with a thickening agent with a ratio of 80:20 and 85:15 to produce biogrease.The statistical analysis showed that the best epoxidation time is 3 hours. Thickening agent affects the texture ofbiogrease. Biogrease with a ratio of base oil with a thickener of 80: 20 has a short fibrous texture (short fibril)with an NLGI value of 3, while biogrease with a ratio of 85: 15 has a brittle texture with an NLGI value of 00. Thebest biogrease produced in this study is biogrease with a ratio of 80:20 with an NLGI value of 3.Keywords: biogrease, palm oil, base oil, RBDPO, epoxidation